Regulatory Role of Host MicroRNAs in Flaviviruses Infection - Cai, Wenjun; Pan, Yuhong; Cheng, Anchun; Wang, Mingshu; Yin, Zhongqiong; Jia, Renyong (Frontiers in Microbiology, 2022)
MicroRNAs (miRNAs) are small non-coding RNA that affect mRNA abundance or translation efficiency by binding to the 3′UTR of the mRNA of the target gene, thereby participating in multiple biological processes, including viral infection. Flavivirus genus consists of small, positive-stranded, single-stranded RNA viruses transmitted by arthropods, especially mosquitoes and ticks. The genus contains several globally significant human/animal pathogens, such as Dengue virus, Japanese encephalitis virus, West Nile virus, Zika virus, Yellow fever virus, Tick-borne encephalitis virus, and Tembusu virus. After flavivirus invades, the expression of host miRNA changes, exerting the immune escape mechanism to create an environment conducive to its survival, and the altered miRNA in turn affects the life cycle of the virus. Accumulated evidence suggests that host miRNAs influence flavivirus replication and host–virus interactions through direct binding of viral genomes or through virus-mediated host transcriptome changes. Furthermore, miRNA can also interweave with other non-coding RNAs, such as long non-coding RNA and circular RNA, to form an interaction network to regulate viral replication. A variety of non-coding RNAs produced by the virus itself exert similar function by interacting with cellular RNA and viral RNA. Understanding the interaction sites between non-coding RNA, especially miRNA, and virus/host genes will help us to find targets for antiviral drugs and viral therapy.